1977
DOI: 10.1128/iai.17.1.91-97.1977
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coccidioides immitis arthrospore, mycelium, and spherule cell walls, and influence of growth medium on mycelial cell wall composition

Abstract: Comparative lipid content, cell wall yield, neutral monosaccharide, glucosamine, and protein (amino acid) contents of arthrospores, mycelia, and spherules ofCoccidioides immitis Cash were studied. Cellular lipid contents were found in the decreasing order: spherules, arthrospores, mycelia. Lipid content of mycelia did not reach the level of arthrospores or spherules even when mycelia were grown on relatively rich media. Cell wall yields of spherules were lower than for mycelia when grown on comparable media. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Heat denaturation, usually associated with a loss of biological activity, generally breaks the ionic and covalent bonds that give proteins their secondary and tertiary struc- (32). The possible presence of cross-linked form of chitin-peptide in C. immitis cell walls was suggested by Wheat et al (34) from their finding that some glucosamine was lost during digestion with pronase. Electrophoresis and silver staining demonstrated 20 bands in the 28-h SE filtrate and 17 bands in the 120-h SE filtrate; mycelial F171 and SF had 5 and 4 bands, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Heat denaturation, usually associated with a loss of biological activity, generally breaks the ionic and covalent bonds that give proteins their secondary and tertiary struc- (32). The possible presence of cross-linked form of chitin-peptide in C. immitis cell walls was suggested by Wheat et al (34) from their finding that some glucosamine was lost during digestion with pronase. Electrophoresis and silver staining demonstrated 20 bands in the 28-h SE filtrate and 17 bands in the 120-h SE filtrate; mycelial F171 and SF had 5 and 4 bands, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…2C). Given the high content of chitin (5 to 22%) in mycelial Coccidioides immitis (29,30), the growth inhibition may have been due to blockage of septum formation as a result of reduced chitin synthesis. However, under the conditions of these assays, nikkomycin Z by itself is not fungicidal for most mycelial isolates of Coccidioides immitis at the concentrations tested and it does not readily affect the MLCs of azoles for most isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have demonstrated that methylated mannose-containing polysaccharides occur in the walls of arthroconidia, spherules, and hyphae of C. immitis (3,31,(35)(36)(37). In addition, previous reports have indicated that the ID-TP antigen is predominantly polysaccharide (13, 17, 41), and partial to total loss of reactivity with IgM precipitin occurs when the antigen is subjected to periodate oxidation (13).…”
Section: 'mentioning
confidence: 99%
“…We also show that reactivity of the antigen with serum samples from patients with coccidioidomycosis is retained after pronase digestion or heating (100°C, 5 min) but is lost after periodate oxidation. Examination of the carbohydrate composition of the TP antibody-reactive antigen (TP-Ag) by gas chromatography-mass spectroscopy revealed 3-0-methylmannose (3-0-MM), a sugar that was previously shown to be a component of immunoreactive fractions of C. immitis (3,15,17,28,(35)(36)(37) and possibly unique to this pathogen among the systemic fungal pathogens (3,37). In this report, we also further examine the serologic reactivity of the 120-kDa TP-Ag and, in particular, the significance of 3-0-MM in precipitin binding to this macromolecule.…”
mentioning
confidence: 99%